Efeects of process variables on mass transfer during osmotic dehydration of ginger slices using carboxymethyl cellulose as an edible coating material - Salim N.S.M.; Kamaruddin K.H.; Mohamad Isa M.I.N. (Universiti Malaysia Terengganu, 2024)
Indexed by Scopus